Effectiveness of Fig Leaf Extract (Ficus Carica L.) in Lowering Blood Glucose in Mice (Mus Musculus) - Aisyah, Nur; TR Dewi, Sisilia; Jumain, Jumain (Riviera Publishing, 2023)
Fig leaves (Ficus carica L.) is a plant that has antidiabetic properties, because fig leaves contain alkaloid compounds, flavonoids, tannins, polyphenols, saponins, terpenoids, and steroids. This study aims to determine the extract of fig leaves (Ficus carica L.) in lowering blood glucose in mice (Mus musculus). Extraction is carried out by maceration with 96% ethanol solvent, then evaporated using Rotavapor. This study used alloxane as a diabetes inducer, the dose of fig leaf extract tested was 5%, 10% and 15% given orally. Observations were made on day 3 and day 7. As a positive control used Glibenclamide and Na. CMC 1% w/v as a negative control. The results showed an average percent reduction in blood glucose levels for negative controls by 18.6%, for 5% extracts by 29.1%, for 10% extracts by 46.6%, for 15% extracts by 83.9% and for positive controls by 45.8%. The results of research have been obtained that the administration of Fig Leaf extract (Ficus carica L.) is proven to reduce blood glucose levels in mice (Mus musculus) induced by alloxane at concentrations of 5%, 10%, 15%. In the One-way ANOVA test, it shows a significant value (p < 0.05) showing a significant difference in each contract. It can be concluded that fig leaves can be a potential alternative treatment for diabetes mellitus with the right concentration can be an effective and natural treatment option.